2017
DOI: 10.1002/2017jd026547
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aerosol composition data for western United States wildfires between 2005 and 2015: Dust emissions, chloride depletion, and most enhanced aerosol constituents

Abstract: This study examines major wildfires in the western United States between 2005 and 2015 to determine which species exhibit the highest percent change in mass concentration on day of peak fire influence relative to preceding nonfire days. Forty‐one fires were examined using the Environmental Protection Agency (EPA) Interagency Monitoring of Protected Visual Environments (IMPROVE) data set. Organic carbon (OC) and elemental carbon (EC) constituents exhibited the highest percent change increase. The sharpest enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
125
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 123 publications
10
125
0
Order By: Relevance
“…Chen et al (2010) showed the release of NO x was also related to combustion condition, with more NO x from the flaming phase and more NH 3 from the smoldering phase. Schlosser et al (2017) also found the concentrations of nitrate, fine soil, and coarse particles increased on peak EC days, that is, their defined smoke-impact days in the western United States from 2005 and 2015, consistent with our results. Other notable differences in the smoke aerosol composition between the two western regions and the SE are the sulfate and soil fractions.…”
Section: Surface Smoke Chemical Compositionsupporting
confidence: 90%
See 2 more Smart Citations
“…Chen et al (2010) showed the release of NO x was also related to combustion condition, with more NO x from the flaming phase and more NH 3 from the smoldering phase. Schlosser et al (2017) also found the concentrations of nitrate, fine soil, and coarse particles increased on peak EC days, that is, their defined smoke-impact days in the western United States from 2005 and 2015, consistent with our results. Other notable differences in the smoke aerosol composition between the two western regions and the SE are the sulfate and soil fractions.…”
Section: Surface Smoke Chemical Compositionsupporting
confidence: 90%
“…This may also explain a greater enhancement of nitrate in the western regions (1.1% in the PW and 1.6% in the SW), where flaming fires may dominate, compared to the SE (0.69%). Schlosser et al (2017) determined smokeimpacted days as days with high EC (mean + 2σ for the 10-week period centered around this day), while our method uses the overlap with HMS and further restricts "smoky days" to the subset with high PM 2.5 loadings (> mean + σ for our selected April-September time frame). The sulfate fraction is 18% in the SE and only 1-3% in the two western regions, which may be due to fuel differences, as discussed earlier.…”
Section: Surface Smoke Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study analyzes a comprehensive set of cloud water samples obtained in the stratocumulus cloud deck off the California coast during the months of July and August between 2011 and 2016. The Center for Interdisciplinary Remotely‐Piloted Aircraft Studies Twin Otter conducted flights in the following four campaigns from which data are analyzed: the Eastern Pacific Emitted Aerosol Cloud Experiment (E‐PEACE) (Russell et al, ; Wonaschütz et al, ), the Nucleation in California Experiment (NiCE) (Crosbie et al, ; Maudlin et al, ), the Biological and Oceanic Atmospheric Study (BOAS) (Wang et al, ), and the Fog and Stratocumulus Evolution (FASE) Experiment (Dadashazar et al, ; Schlosser et al, ). Table summarizes the dates and flights for these field experiments, while Figure shows the spatial area of the flight tracks during each experiment.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The plume was transported offshore on a number of the flights and was likely to be a significant conduit for lofting near surface continental airmasses into the lower free troposphere, where it could later descend into the marine cloud deck. It is also known that fires 30 can locally drive substantial dust and soil emissions (Kavouras et al, 2012, Diapouli et al, 2014, Schlosser et al, 2017. Comparing the Ca 2+ :Na + ratio between probes shows that RF4 exhibits a marked difference in the relative abundance of non-sea salt calcium compared to the other flights.…”
mentioning
confidence: 99%